African developments: the comprehensive Africa Agriculture Development Programme (CAADP) is an opportunity for African agriculture - Michael Brüntrup (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Agriculture is a sector significant for economic growth and the reduction of poverty and hunger in Africa. The Comprehensive Africa Agriculture Development Programme (CAADP) is Africa's attempt to self-reliantly re-activate the agricultural sector. In the framework of the African Union (AU), all member states committed to generate at least 6% growth in the agricultural sector, and to invest at least 10% of their national budgets to that end. The CAADP has further formulated rules for improving agricultural policy and sector investment planning and offers forums for dialogue with other African nations and the international community of donors. After initially low beginnings, the first 20 countries have taken the first hurdle, i.e. signing national compacts. The next steps at the national and regional levels, such as formulating investment plans, are following rapidly, and at least some agricultural budgets are increasing. The CAADP is far from realising its potential. What it clearly has achieved is making the African agricultural sector visible at the international level. At the continental and regional levels, the CAADP has created useful structures. However, these have yet to demonstrate their value. The processes that were created are now so far advanced at the all-important national level that their application raises expectations for significant improvements in agricultural planning. However, implementation is in its infancy and the value of older CAADP processes is somewhat doubtful. To become successful, the CAADP needs to: Continue the strategy of international visibility; Avoid building parallel structures and emphasise the support of existing national policy processes; Not only encourage investment, but particularly quality aspects in agricultural policy (governance); Enforce monitoring and evaluation; Emphasise transparency and communication. Donors can support the CAADP by adopting its principles and demand that countries comply with them, as well as supporting the continental, regional and most importantly national capacities along the lines of the projected CAADP initiatives. Support must become more reliable and sustainable, because if the CAADP fails, that would not only harm the AU, it would also reinforce the reputation of the African agricultural sector as being beyond reform.
Keywords: 330